Relative Functions of Gαs and its Extra-large Variant XLαs in the Endocrine System - Bastepe, M. (Hormone and Metabolic Research, 2012)
Gαs is a ubiquitous signaling protein necessary for the actions of many neurotransmitters, hormones, and autocrine/paracrine factors. Loss-of-function mutations within the gene encoding Gαs, GNAS, are responsible for multiple human diseases, including Albright’s Hereditary Osteodystrophy, progressive osseous heteroplasia, and pseudohypoparathyroidism. Gain-of-function mutations in the same gene are found in various endocrine and nonendocrine tumors and in patients with McCune-Albright Syndrome and fibrous dysplasia of bone. In addition to Gαs, GNAS gives rise to multiple additional coding and noncoding transcripts. Among those, XLαs is a paternally expressed product that is partially identical to Gαs. This article reviews the cellular actions of Gαs and XLαs, focusing on the significance of XLαs relative to Gαs in mammalian physiology and human disease.
Keywords: bone; parathyroid hormone; hypothyroidism; hypocalcemia; hypogonadism